CONVOLVULUS PLURICAULIS AS A COGNITION BOOSTER: RELEVANCE TO ALZHEIMER’S DISEASE (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The herbal medicinal plant, Convolvulus pluricaulis: a rasayana drug has been primarily advocated for use in mental stimulation and rejuvenation therapy. In ancient systems of Indian medicine, Ayurveda, the plant is also known by the name Shankhpushpi and has been shown to act as a prominent memory improving drug, a psychostimulant and tranquiliser. The plant displays its biological activity due to the presence of several alkaloids, flavanoids and coumarins as active chemicals. Previous reports by us and others have demonstrated beneficial effect of extracts of this plant in an in-vitro and in-vivo models of Alzheimer’s disease (AD). Justification of its potential for an ancient brain tonic has been provided recently by clinical studies on polyherbal formulation of this plant. This review attempts to compile information on Convolvulus Pluricaulis in order to establish this herbal drug as a potent natural therapeutic agent to combat AD related symptoms.